Development of a reflection during work above a self-portrait (Pedagogy of Higher and Secondary Education, 2007)
In the article an author examines the concept of reflection in philosophical, psychological, pedagogical aspects. Implementation ofeducational-creative works in the genre of self-portrait is shown as mean of development of reflection of future teachers of fine art.
Keywords: reflection; self-knowledge; self-examination; self-appraisal; self-portrait